Understanding the Impact of Infection, Inflammation, and Their Persistence in the Pathogenesis of Bronchopulmonary Dysplasia - Balany, Jherna; Bhandari, Vineet (Frontiers in Medicine, 2015)
The concerted interaction of genetic and environmental factors act on the preterm human immature lung with inflammation being the common denominator leading to the multifactorial origin of the most common chronic lung disease in infants – bronchopulmonary dysplasia or BPD. Adverse perinatal exposure to infection/inflammation with added insults like invasive mechanical ventilation, exposure to hyperoxia and sepsis causes persistent immune dysregulation. In this review article we have attempted to analyze and consolidate current knowledge about the role played by persistent prenatal and postnatal inflammation in the pathogenesis of BPD. While some parameters of the early inflammatory response (neutrophils, cytokines etc.) may not be detectable after days to weeks of exposure to noxious stimuli, they have already initiated the signaling pathways of the inflammatory process / immune cascade and have affected permanent defects structurally and functionally in the BPD lungs. Hence translational research aimed at prevention / amelioration of BPD needs to focus on dampening the inflammatory response at an early stage to prevent the cascade of events leading to lung injury with impaired healing resulting in the pathologic pulmonary phenotype of alveolar simplification and dysregulated vascularization characteristic of BPD.